Chocolate hypersensitivity is not common in children with atopic dermatitis. - Falconieri, P.; Arcese, G.; Ziruolo, G.; Businco, L. (European Journal of Pediatric Dermatology, 2018)
We investigated symptomatic sensitization to chocolate in forty-eight children with atopic dermatitis. Each patient was tested with prick skin tests for cow's milk, egg, wheat, codfish, soy and chocolate. Open challenge test to chocolate was carried out and doubleblind placebo-controlled food challenges were performed when the response to the open challenge was not conclusive. Prick skin tests to chocolate were negative in all subjects. Challenge tests to chocolate gave negative results both for immediate and late reactions in all 48 children. No child experienced adverse reactions to chocolate or worsening of atopic dermatitis. We concluded that chocolate hypersensitivity is not common in children affected by atopic dermatitis and reactions after chocolate ingestion may be due to ingredients other than chocolate.